Application of Smart Oven Technology as an Effort to Increase Smoked Egg Production and Quality in Sania MSME - Yena Arifa; Nurul Humaidah; Feri Widodo; Muhammad Muizzhuddin; Bibit Pranoto (Journal of Community Practice and Social Welfare, 2021)
Mitra Home salted egg industry SANIA MSME is an MSME that engages in duck cultivation and the production of Smoked Salted Eggs. SANIA MSME was founded by a duck breeder group in 2008 in Kawedusan Ponggok Village, Blitar. Smoked salted eggs are known for their burnt/smoky aroma and greasy egg yolks. Smoked egg production is done manually using the use of smoking drums. These manual devices are only capable of baking 150 grains per day. Meanwhile, damage due to smoking with an oven drum can reach up to 15-20%. This can reduce profits by up to 20% per cycle of the smoking process. Damage occurs when users forget or are too late to lower the drum oven's temperature before it reaches temperatures of 1000C or more. The uneven heat can also result in a reduction to taste and greasiness of the egg yolks. Manual ovens take 7-10 hours at 80-900C to cook. From discussions with partners, it was discovered that they needed egg smoking ovens that feature thermoregulators and can produce even flows of smoke automatically. There is a need for technological innovation in the egg fumigation equipment category in the form of smart egg smoking ovens complete with thermoregulators and automatic smoke airflow systems. Smart ovens have the potential to increase productivity by 75% with a faster smoking process of 3-4 hours. The service method was carried out by way of producing a design for smart ovens, socialization and assistance in the use of the device, assistance in the production of smoked eggs, and program evaluation. The results of the mentoring activity suggested that the production of smoked eggs can increase by 70% with the level of cooking damage sitting at less than 10% and an improvement in the product's taste.